(untitled) (Journal of Social Sciences Review, 2023)
The goal of this study is to examine the effective international system between Pakistan and China for the elimination of piracy. From the standpoint of general international law, this study investigates these processes concerning the crimes of robbery and piracy at the ocean. This study examines the relevance of the procedures placed on the continental strategy, with a focus on the form of such offenses. From the standpoint of global public international law, this study investigates such processes concerning the crimes of robbery and piracy at the ocean. This study demonstrates the relevance of the processes placed on the continental strategy, with special emphasis on the form of such crimes. Countries have evolved to build systems of multilateral community to be executed in the disputed sea since marine criminal actions are increasingly perpetrated beyond boundaries. It concludes that given the aforementioned legislative framework, nations are free to achieve diverse goals like ensuring navigational safety, preserving stability, or defending economic growth. Nevertheless, this does not substantially change the character of the zonal method. However, establishing a conversation platform among coastlines and user states improves marine control of maritime borders.